Home as a mixture of spaces during the COVID-19 pandemic: The case of migrant families in Poland - Popyk, Anzhela (Kultura i Społeczeństwo, 2021)
The spread of the coronavirus has led to significant modifications in the majority of social and private institutions. For most families, home is now the location of many activities that are usually kept separate, such as work, school, entertainment, and socialising. Migrant families, for whom the school was the primary place for socialising, were forced to “host” school at home. As a result, migrant families’ homes have been reconstructed from a private household and intimate dwelling place into a mixture of spaces. This paper applies the theory of social diffusion developed by Dodd and Winthrop, and the concept of social solvation designed by Sarnowska et al., to study the diffusion of places at the time of lockdown. The data are derived from a qualitative study of migrant families in Poland during the school shutdown. This study investigates how the mixture of various places within the home has affected the lives of family members.